2018
DOI: 10.1590/0004-282x20180023
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline and intraoral devices for migraine prevention: a randomized comparative trial

Abstract: Amitriptyline proved superior to the NTI-tss and the non-occlusal splint. Despite its approval by the United States Food and Drug Administration, the NTI-tss was not superior to a sham device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…[18] Disocclusion or any high contact during occlusion creates an imbalance in the relaxation of the masticatory muscles considering their role in maximal intercuspation and in centric relation. [19] The relieve of the high contacts to attain an occlusal equilibration helps in relieving the symptoms the TMD's. [7,20] In addition, intra-oral splints either alone or in combination with other approaches are often used to reduce pain and improve function in patients with myofascial pain.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Disocclusion or any high contact during occlusion creates an imbalance in the relaxation of the masticatory muscles considering their role in maximal intercuspation and in centric relation. [19] The relieve of the high contacts to attain an occlusal equilibration helps in relieving the symptoms the TMD's. [7,20] In addition, intra-oral splints either alone or in combination with other approaches are often used to reduce pain and improve function in patients with myofascial pain.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the use of TCAs for chronic migraine [39], insomnia [40,41], alcohol use disorder [42,43], and neuropathic corneal pain has been conducted with indications of therapeutic efficacy, though adverse effects remain a concern.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%
“…To date, most studies show no additional benefit in comparing ACs with FPs. Furthermore, headache studies have shown that there was minimal effect in improvement of migraine headaches using ACs when compared to low dose tricyclic antidepressant medication (38). There have been both one MAUDE database report and anecdotal evidence to indicate that these appliances even worn just at night can cause occlusal changes with resulting anterior open bite.…”
Section: Anterior Only Contacting Oas (Acs)mentioning
confidence: 99%